2018
DOI: 10.3329/jninb.v3i2.36773
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Biochemical and Hormonal Profile of Polycystic Ovary Syndrome

Abstract: Background:The polycystic ovary syndrome is a heterogenous condition, the pathophysiology of which is multifactorial. It is considered as a systemic and metabolic disorder like hyperglycemia and insulin resistance with increased risk of type II diabetes mellitus and cardiovascular diseases. Objective: The purpose of the present study was to analyze the clinical, biochemical and hormonal profile of patients PCOS and to find out correlations among them. Methodology: This cross-sectional observational study was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…As per selection criteria 50 patients diagnosed as polycystic ovarian disease and 50 healthy controls were enrolled for this study as per selection criteria. 16 Tosi et al has demonstrated that insulin resistance, as assessed by the glucose clamp technique, is a very common feature in women with PCOS, even in normalweight subjects this finding supports our study. 17 Goodarzi et al has reported that substantial heritabilities of APAs, particularly DHEAS, have been found in the general population and in women with PCOS that supports our study.…”
Section: Resultssupporting
confidence: 92%
“…As per selection criteria 50 patients diagnosed as polycystic ovarian disease and 50 healthy controls were enrolled for this study as per selection criteria. 16 Tosi et al has demonstrated that insulin resistance, as assessed by the glucose clamp technique, is a very common feature in women with PCOS, even in normalweight subjects this finding supports our study. 17 Goodarzi et al has reported that substantial heritabilities of APAs, particularly DHEAS, have been found in the general population and in women with PCOS that supports our study.…”
Section: Resultssupporting
confidence: 92%
“…These elevated LH levels can harm the endometrium and oocytes by creating an unfavourable environment [13]. In more than half (52%) of the cases, LH to FSH ratio was found >2 by Nahar et al [14]. This is consistent with Begum et al findings (51%) [12].…”
Section: Discussionsupporting
confidence: 78%
“…It is characterized by polycystic ovaries, hyperandrogenism, and chronic anovulation, and is regarded as a multifactorial disorder because of its genetic and environmental onset [2,3]. Due to its systemic and metabolic pathogenesis, the risk of cardiovascular diseases, insulin resistance (IR), type II diabetes mellitus (DM), hyperinsulinemia, and dyslipidemia may increase in these patients [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Women with PCOS have hyperinsulinemia, which influences the hypothalamic-pituitary-gonadal axis, enhancing the luteinizing hormone (LH) secretion over follicle-stimulating hormone (FSH), reducing follicular maturation and sex hormone-binding globulin (SHBG), and producing ovarian androgen [ 4 ]. In addition, women with PCOS are at higher risk of other metabolic diseases such as obesity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%